PENGARUH SOCIAL MEDIA MARKETING DAN INOVASI PRODUK TERHADAP MINAT BELI KONSUMEN (Studi Kasus Pada Toko Jaya Rasa Bengkulu) - Permata Sari, Reka; Islamuddin, Islamuddin (Yayasan Insani Mandiri Santani, 2024)
The title of this research is The Effect of Social Media Marketing and Product Innovation on Consumer Purchase Interest (Case Study at Toko Jaya Rasa Bengkulu). This study aims to determine which factors are most dominant in influencing consumer buying interest, the research was conducted from November 2023 to March 2024.The sample of this research is consumers who have bought products and know Toko Jaya Rasa Bengkulu city from social media. This research uses quantitative methods on 140 respondents. The sampling technique is accidental sampling, the method used in this research is quantitative method with Multiple Linear Regression analysis. Based on the results of multiple linear regression, the regression equation Y= 3.427 + 0.387 (X1), + 0.289 (X2) and the coefficient of determination R Square (R2) obtained a value of 0.510 or around (51.0%). The research results and hypotheses in this study indicate that social media marketing variables and product innovation have a positive effect partially or simultaneously on buying interest in Toko Jaya Rasa Bengkulu. Keywords: Social Media Marketing, Product Innovation, Purchase Interest